If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(y+7)=-1
We move all terms to the left:
-(y+7)-(-1)=0
We add all the numbers together, and all the variables
-(y+7)+1=0
We get rid of parentheses
-y-7+1=0
We add all the numbers together, and all the variables
-1y-6=0
We move all terms containing y to the left, all other terms to the right
-y=6
y=6/-1
y=-6
| q-5/2=2 | | -4(8-3x)=6x | | 4(v+13)=20 | | 2(d+2)=6 | | 5(m-(2))+36=-4 | | 2x^2+3x+-12=8 | | 10x32x=4 | | 19x-7=183 | | 16-4=n/3 | | x/3-7=5/2 | | -14(2x-5)=630 | | 67=y−37 | | ?x5-28=117 | | 138-2x=108 | | 0=x^2-92x+360 | | x+146=180 | | 12x+8-6x=-70 | | w-18=12 | | 5x=12=11 | | -2+g=9 | | a÷5+3=9 | | 4(x+2)=14–2(3–2x) | | 10f=100 | | 12-h-12=17-12 | | -6y+8=-16 | | n/3-4=16 | | 14u2+23u+3=0 | | n/3-3=16 | | S=-16t^2+20t+7 | | 14u2+23u=3 | | S=-16t^2+28t+9 | | -6y+3=-57 |